2011
DOI: 10.1111/j.1365-2435.2011.01911.x
|View full text |Cite
|
Sign up to set email alerts
|

Host plant variation plastically impacts different traits of the immune system of a phytophagous insect

Abstract: Summary1. Host plant quality affects herbivorous insect performance and consequently their susceptibility to natural enemies. Recently, it has been hypothesized that the immune function of herbivorous insects can be altered by their host plant, thus generating variation in their susceptibility to entomopathogens. Previous studies testing this hypothesis provided contradictory outcomes, mainly as a result of the differences in methodology such as measuring a single-immune parameter rather than considering trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 45 publications
3
44
0
Order By: Relevance
“…Readings were obtained every 30s at 490nm. Enzyme activity was measured as the slope of the reaction curve during the linear phase of the reaction (linear regression with R 2 >0.8) and reported as the increase in optical density (ΔOD) per minute and per microliter of haemolymph (Vogelweith et al, 2011).…”
Section: Measurement Of Immune Defensementioning
confidence: 99%
“…Readings were obtained every 30s at 490nm. Enzyme activity was measured as the slope of the reaction curve during the linear phase of the reaction (linear regression with R 2 >0.8) and reported as the increase in optical density (ΔOD) per minute and per microliter of haemolymph (Vogelweith et al, 2011).…”
Section: Measurement Of Immune Defensementioning
confidence: 99%
“…The results of this study could have implications for the evolution of plant–herbivore–parasitoid interactions and emphasize the important role of the immune system and its variation based on host plant variation in bottom-up processes involving plants26. All in all, the role of elevated atmosphere CO 2 in the herbivore insect immune function is poorly known, definitely requiring further investigation.…”
Section: Discussionmentioning
confidence: 90%
“…Host plant can significantly influence the growth and condition of insects [19,35]. Previous experiments have examined the fecundity and longevity of adult whiteflies that were reared on cotton from egg to adult and transferred onto tobacco plants [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…ERKs are involved in the regulation of meiosis, mitosis and post mitotic functions in differentiated cells, while JNK and p38 are critical for the stress-related signal transduction pathways conveying signals from the cell surface into the nucleus to initiate gene expression [15,16]. Previous studies found that JNK may be involved in cellular response to environmental stresses [1719] and immune defense to virus and bacteria [16,20,21]. …”
Section: Introductionmentioning
confidence: 99%